Effectiveness of an Educational Program on the Knowledge of Parents of Children with Type 1 Diabetes Mellitus about Methods of Insulin Injection in Specialized Diabetic and Endocrine Glands Center at Al-Nasiriyah City - Dakhel Rashak, Eman; Abed Neamah, Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
Background: Diabetes mellitus is one of the world’s oldest known diseases. Diabetes mellitus (DM) is a clinical syndrome characterized by hyperglycemia. Type 1 diabetes mellitus (T1DM) is the most common chronic metabolic disease in childhood. Diabetics and their families have to learn a wide variety of technical and cognitive skills to maintain good glycemic control. Objectives: Determine the effect of the health education program in enhancing the knowledge of parents of children with type 1 diabetes mellitus about methods of insulin injection. Methodology: The study was designed as a quasi-experiment for a study group (30) and a control group (30) participants, parents of children with type 1 diabetes mellitus, being tested in three periods: pre-test, post-test-1, and post-test-2. The study group participants are tested prior to implementing the educational program (the educational program lectures started from 3rd–5th February 2020). Then after a period, they are tested post-test-1 (on 9th February 2020), and after a while, post-test-2 was conducted (on 24th February 2020). The control group participants are provided with the same questionnaire to answer. The pre-test was conducted at the same time as the pre-test of the study group, while post-test-1 was conducted (on 10th February 2020) and post-test-2 was conducted (on 25th February 2020), but without enrollment in the educational program. Results: The study outcomes include a low assessment of parents’ knowledge prior to the educational program, which became a high assessment after participation in the program. This does not apply to the control group, in which participants remained within low assessment for three testing periods. Conclusion: Parents’ knowledge regarding methods of insulin injection improved after the implementation of the educational program in the study group, revealing that the effectiveness of the provided program was highly beneficial. Recommendations: Encouraging parents for more involvement in seminars and educational sessions on diabetes mellitus, especially the methods of insulin injection and how to deal with a sick child.